Enhanced removal of Cr (VI) from aqueous solution by mesoporous activated carbons. (16th December 2014) - Fan, Mingxia; Tong, Shitang; Jia, Charles Q.
The capability of mesoporous activated carbons (MACs) to adsorb Cr (VI) in aqueous solution was investigated. The MACs were prepared in the lab from upgraded coal tar pitch using the nano-sized imprinting method. Adsorption of Cr (VI) was found to be dependent on the solution pH. The adsorption kinetic data was found to fit well with a pseudo-second-order rate equation. Three adsorption isotherm models were used to analyse the equilibrium data. Removal of Cr (VI) increased with an increase in mesoporosity of MACs, highlighting the importance of mesoporosity in enhancing adsorption efficiency. The major surface oxygen groups were carboxylic, lactonic and hydroxyl. X-ray photoelectron spectroscopy analysis was employed to investigate the sorption mechanism. It was revealed that a portion of Cr (VI) was adsorbed via electrostatic interaction, while the rest was adsorbed in the reduced form (Cr (III)) which was most likely bound to surface oxygen groups on the MAC.